PENINGKATAN PENGETAHUAN GIZI ANAK PRA-SEKOLAH DI DESA TALLAMBALAO MELALUI PEMANFAATAN TEKNOLOGI INFORMASI BERBASIS APLIKASI ANDROID DAN WEB N TEKNOLOGI INFORMASI BERBASIS APLIKASI ANDROID DAN WEB - Yanti, Reski Wahyu; Seppewali, Andi; Fardina, Fardina; Page, Muhammad Taufik; Yusuf, Andi M.; Saidy, Hamdy Nur; Musawwir, Musawwir; Salim, Salim (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
The issue of nutrition among preschool children in Tallambalao Village, Majene Regency, has become a primary concern due to the low public understanding of healthy eating habits and limited access to health information. This situation is further exacerbated by the lack of support from healthcare workers and village officials in regularly monitoring the nutritional status of children. This program is designed to improve the community's knowledge of nutrition while also facilitating the evaluation of children's nutritional status through the use of easily accessible Android and web-based information technology applications. The program's implementation involves educating parents, village officials, and healthcare workers. Activities include introducing an application to monitor children's nutritional status, managing data digitally, and integrating information with a web-based system. By combining technology-based approaches with community empowerment, this program is expected to have a significant positive impact, both in terms of improving public health quality and developing human resources in Tallambalao Village.